2016
DOI: 10.1589/jpts.28.983
|View full text |Cite
|
Sign up to set email alerts
|

Exercise intervention as a protective modulator against metabolic disorders in cigarette smokers

Abstract: [Purpose] assess the impact of exercise intensity on desire to smoke, serum cotinine, stress hormones, total antioxidant capacity, and oxidative free radicals as potential markers of cardiopulmonary metabolic disorders were measured.in cigarette smokers. [Subjects and Methods] The participants (150 randomly selected healthy men, aged 18–55 years) were classified into 4 smoking groups: control (non-smokers; N= 30); mild (N = 33); moderate (N = 42), and heavy (N = 45). The participants were assigned to either mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…Another study demonstrated that current smokers of ve or more cigarettes/day showed signi cantly higher levels of testosterone [55]. Signi cant increases in serum testosterone levels were observed in smokers group [56]. Similarly, Johan et al observed that smoking men had 15% higher total testosterone levels compared with non-smoker [57], which was also demonstrated among current smokers It is important to emphasize that our study has two limitations.…”
Section: Discussionsupporting
confidence: 55%
“…Another study demonstrated that current smokers of ve or more cigarettes/day showed signi cantly higher levels of testosterone [55]. Signi cant increases in serum testosterone levels were observed in smokers group [56]. Similarly, Johan et al observed that smoking men had 15% higher total testosterone levels compared with non-smoker [57], which was also demonstrated among current smokers It is important to emphasize that our study has two limitations.…”
Section: Discussionsupporting
confidence: 55%
“…Another study demonstrated that current smokers of ve or more cigarettes/day showed signi cantly higher levels of testosterone [54]. Furthermore, signi cant increases in serum testosterone level were observed in smokers group [55].…”
Section: Discussionmentioning
confidence: 93%
“…Another study demonstrated that current smokers of five or more cigarettes/day showed significantly higher levels of testosterone [ 55 ]. Significant increases in serum testosterone levels were observed in smokers group [ 56 ]. Similarly, Johan et al observed that smoking men had 15% higher total testosterone levels compared with non-smoker [ 57 ], which was also demonstrated among current smokers [ 47 ].…”
Section: Discussionmentioning
confidence: 99%